The trace of translators’ ideology: a case study of English translations of the Qur’an - Mohaghegh, Ameneh; Pirnajmuddin, Hossein (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
The present article attempts to explore the effect of translator's ideology on the translated text by focusing on the English translations of two Qura'nic verses from surah Al-Taubah (Repentance) and surah Al-Anfal (The Spoils of War) that are most often referred to with the purpose of imaging Islam as the religion of violence and intolerance. Two parts of the article are devoted to definitions of ideology and the relationship between ideology and translation. The last part takes on board the works of four translators with different religions and ideologies who lived in different time periods and are as follows: one Iranian Muslim translator (Tahereh Saffarzade); one English Muslim translator (Mohammad M. Pickthall) and two English Christian translators (Arthur J. Arberry and George Sale). It is argued that Saffarzadeh as a Muslim and the most recent translator among the ones discussed seems to have been more aware of debates on these verses in comparison with others and as a result more careful in rendering them while Sale's translation is the most ideologically-biased one. The result is indicative of the fact that not only the translators’ attitude towards Islam but also the social context around them can subtly display itself in the renderings.